PERANAN MAJALAH KAMPUS DALAM PENiNGKATAN PROSES BELAJAR MENGAJAR PADA PERGURUAN TINGGI MASA KINI DAN MASA YANG AKAN DATANG - Siswanto, Siswanto (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
The campus  magazine   is a  published  media  by  campus  community,neither by ifs universitynor by student institute.Thereare some types of ifs magazine   as  like  :    The Campus   News/  Popular Scientist Magazine/· Journal and Student Magazines.The  campus   magazine   as  a  good   potential   to  benefit  of  campus community especially to lecturer. One of the measure to know the qualityof  the  lecturer  is  the  scientist  writing sk,11  published  in  the  campusmagazine.The contents  of scientist writing is result of research   new idea  of any discipline scientific and  other relevant inventions. Based on  the  above information  the  position  of  the  campus  magazine  is very strategic  to developing  of sciences and as a barometer the success of a universityin any discipline.